Evaluation of the effectiveness of a joint general practitioner-pharmacist intervention on the implementation of benzodiazepine deprescribing in older adults (BESTOPH-MG trial): protocol for a cluster-randomized controlled trial - Huon, Jean-François; Nizet, Pierre; Caillet, Pascal; Lecompte, Hélène; Victorri-Vigneau, Caroline; Fournier, Jean-Pascal; , the BESTOPH-MG consortium; Flet, Laurent; Corbineau, Erwan; Gallin-Castagne, Alexandra; Lebeaupin, Maxime; Moret, Leïla; et al. (Frontiers in Medicine, 2023)
Background Deprescribing benzodiazepines and related drugs (BZDR) is a challenge due to a lack of time on physicians’ part, a lack of involvement of other health professionals, and the need for adapted tools. This study is based on primary care collaboration, by evaluating the effectiveness of a joint intervention between general practitioners and community pharmacists on the implementation of BZDR deprescribing in older adults. Methods This is a cluster randomized controlled trial in which each cluster will be formed by a physician-pharmacist pair. Within a cluster allocated to the intervention, the pharmacist will be trained in motivational interviewing (MI), and will offer the patient 3 interviews after inclusion by the physician. They will base their intervention on validated deprescribing guidelines. The pharmacist will receive methodological support during the first interviews. Interprofessional collaboration will be encouraged by writing reports for the physician after each interview. The following implementation outcomes will be evaluated: acceptability/adoption, appropriateness, cost, and fidelity. They will be measured by means of sociological interviews, observations, logbooks, and cost-utility analysis. Focus groups with physicians and pharmacists will be carried out to identify levers and barriers experienced in this collaboration. Observations will be conducted with pharmacists to assess their approach of the MIs. Effectiveness outcomes will be based on medication (discontinuation or reduction of BZDR) and clinical outcomes (such as quality of life, insomnia or anxiety), assessed by health insurance databases and validated questionnaires. Discussion This study will determine whether collaboration in primary care between physicians and pharmacists, as well as training and coaching of pharmacists in motivational interviewing, allows the implementation of BZDR deprescribing in the older adults. This study will provide an understanding of the processes used to implement deprescribing guidelines, and the contribution of collaborative practice in implementing BZDR discontinuation. The cluster methodology will allow to assess the experience of the relationship between the different primary care actors, and the related obstacles and levers. The results obtained will make it possible to produce guidelines on the involvement of community pharmacists in the management of substance abuse in older adults, or even to legislate new missions or care pathways. Clinical trial registration ClinicalTrials.gov, identifier, NCT05765656.